Interrelationships between changes in erythropoietin, plasma volume, haemoglobin concentration, and total haemoglobin mass in endurance athletes - Sitkowski, D.; Szygula, Z.; Pokrywka, A.; Turowski, D.; Malczewska-Lenczowska, J. (Research in Sports Medicine, 2018)
Interrelationships between physiological changes (Delta) in erythropoietin (EPO), plasma volume (PV), haemoglobin concentration ([Hb]), and total haemoglobin mass (tHb-mass) were examined in cyclists who trained in different altitudes. Regardless of differences in pattern of changes observed in three training locations, DeltaEPO was correlated positively with DeltaPV, negatively with Delta[Hb], and trivially with DeltatHb-mass. Delta[Hb] was negatively correlated with DeltaPV. In the pooled data the Spearman`s rank correlation coefficients were as follows: r = 0.783, P < 0.001; r = -0.704, P < 0.001; r = 0.136, P > 0.05; r = -0.813, P < 0.001, respectively. The obtained results have shown that EPO does not only regulate [Hb] by erythropoiesis stimulation but also by PV modulation, which probably aims at keeping proper level of arterial oxygen content for oxygen delivery to tissues.